El sistema de rehabilitación en los centros de privación de libertad y su incidencia en los derechos fundamentales. - Osorio Hidalgo, Leonel Alcides (2015)
This legal research work entitled "SYSTEM REHABILITATION CENTERS OF DEPRIVATION OF LIBERTY AND ITS IMPACT ON FUNDAMENTAL RIGHTS" with its respective proposal; insert a clause to article 695 of the Penal Code of Integral, in order to help ensure effective rehabilitation and reintegration through a labor education program as a mechanism for the rehabilitation and development of persons deprived of liberty of Social Rehabilitation Centers Ecuador. This Legal Research is structured into six chapters. In the first chapter, the main part is exposed in relation to the knowledge of the problem and the effect it was necessary to pose the following hypothesis: "By increasing a paragraph to art. Integral 695 of the Code of Criminal Procedure, may safeguard the rights of people who have served sentence in Ecuador so they can reintegrate into society as productive entities. The second chapter refers to the Theoretical Framework in aspects: Historical, Doctrinal and Legal. In the third chapter the methodology used in the investigation at issue described; the methods used, the types of research, people, samples of techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained through interviews with authorities in laws, in addition to surveys of lawyers in free practice. The fifth chapter describes the conclusions and recommendations, the first that shows the negative part of the problem and the second in which we are proposing a form of solution. Finally the sixth chapter discusses the proposal and that we can do to reintegrate into society of persons deprived of their liberty who are serving and have served condemned, etc.